The Influence of NPL, LDR, BOPO, and CAR on Financial Performance with Institutional Ownership as a Moderating Variable - Pramadani, Karina Aliyyah (CV ODIS, 2024)
The aim of this research is to determine the factors that influence the financial performance of digital banks during the period 2018-2022. The methodology of this research involves the use of purposive sampling to select a sample of 10 digital banks listed with the Financial Services Authority (OJK) for the period 2018-2022. Data analysis techniques include panel data regression and moderation regression to assess the effects of NPL, LDR, BOPO, and CAR on financial performance, with institutional ownership as a moderating variable. The research findings indicate that BOPO and CAR have a positive impact on financial performance, while NPL and LDR have a negative impact. Additionally, institutional ownership does not moderate the relationship between NPL, LDR, and CAR with financial performance. The theoretical contribution of this research lies in its demonstration of how operational efficiency (BOPO) and capital adequacy (CAR) positively influence financial performance, while non-performing loans (NPL) and loan-to-deposit ratio (LDR) negatively impact it. Furthermore, the study reveals that institutional ownership does not moderate the relationships between these variables and financial performance, providing new insights into the dynamics of digital banks and the roles of various financial metrics in influencing their success.